The Mythos moment. (Economist, 2026)
The article argues that the era of unfettered artificial intelligence development in America is ending due to national security fears, triggered by a powerful new model capable of finding software vulnerabilities, forcing a shift from laissez-faire to potential regulation. Topics include artificial intelligence governance, national security risks from technology; and historical comparisons to industrial monopolies.